TMPRSS3 Gene Variants With Implications for Auditory Treatment and Counseling - Moon, In Seok; Grant, Andrew R.; Sagi, Varun; Rehm, Heidi L.; Stankovic, Konstantina M. (Frontiers in Genetics, 2021)
Objective: To identify and report novel variants in the TMPRSS3 gene and their clinical manifestations related to hearing loss as well as intervention outcomes. This information will be helpful for genetic counseling and treatment planning for these patients. Methods: Literature review of previously reported TMPRSS3 variants was conducted. Reported variants and associated clinical information was compiled. Additionally, cohort data from 18 patients, and their families, with a positive result for TMPRSS3-associated hearing loss were analyzed. Genetic testing included sequencing and copy number variation (CNV) analysis of TMPRSS3 and the Laboratory for Molecular Medicine’s OtoGenome-v1, -v2, or -v3 panels. Clinical data regarding patient hearing rehabilitation was interpreted along with their genetic testing results and in the context of previously reported cochlear implant outcomes in individuals with TMPRSS3 variants. Results: There have been 88 previously reported TMPRSS3 variants associated with non-syndromic hearing loss in more than 20 ancestral groups worldwide. Here we report occurrences of known variants as well as one novel variant: deletion of Exons 1-5 & 13 identified from our cohort of 18 patients. The hearing impairment in many of these families was consistent with that of previously reported patients with TMPRSS3 variants (i.e. typical down-sloping audiogram). Four patients from our cohort underwent cochlear implantation. Conclusion: Bi-allelic variants of TMPRSS3 are associated with down-sloping hearing loss regardless of ancestry. The outcome following cochlear implantation in patients with variants of TMPRSS3 is excellent. Therefore, cochlear implantation is strongly recommended for hearing rehabilitation in these patients.